Muqarnas : an annual on the visual culture of the Islamic world. - Bailey, Julia, 1944-; Necipoğlu, Gülru. (Muqarnas, 2008)
Muqarnas is sponsored by The Aga Khan Program for Islamic Architecture at Harvard University and the Massachusetts Institute of Technology, Cambridge, Massachusetts. In Muqarnas articles are being published on all aspects of Islamic visual culture, historical and contemporary, as well as articles dealing with unpublished textual primary sources.